A quantitative test for heat-induced cell necrosis in vascular cambium and secondary phloem of Eucalyptus obliqua stems. (21st November 2020) - Subasinghe Achchige, Yasika Medhavi; Volkova, Liubov; Drinnan, Andrew; Weston, Christopher J
Abstract: Aims: Exposure of Eucalyptus tree stems to the radiant heat of forest fires can kill cambial cells and their embedded regenerative meristems, thus preventing epicormic resprouting and recovery of the tree. Currently, there is no tissue-level method to quantify the viability of cambial cells in Eucalyptus following heat exposure. The first aim of this study was to adapt and validate the tetrazolium reduction method of testing for cell viability in Eucalyptus . The second aim was to apply the method to establish a threshold level of cambium cell viability in Eucalyptus obliqua to enable the identification of a critical temperature. Methods: The study used the tetrazolium reduction method to quantitatively determine phloem–cambium cell viability in Eucalyptus . Circular sections of bark with underlying phloem and cambium were cut from mature E. obliqua and samples ranging in mass from 1 to 30 mg were exposed for 1 min to temperature treatments ranging from 20 to 85 °C and kept for 20–22 h at room temperature in 0.8% 2, 3, 5-triphenyl tetrazolium chloride (TTC) to test for cell viability. The 1, 3, 5-triphenyl tetrazolium formazan (TPF) formed was cold extracted with ethanol and quantified as absorbance at 485 nm. Important Findings: The TTC reduction method reliably quantified a decline in cell viability with rising temperature in tissue sections that included vascular cambium, and identified 60 °C as the critical temperature for cambium–phloem cells of Eucalyptus species. Cell viability, calculated as [TPF Treatment °C]/[TPF 20 °C], declined by 90% between 20 and 85 °C. The cell viability results confirmed that significant tissue necrosis occurred in Eucalyptus at temperatures between 50 and 70 °C, after 1 min of in vitro tissue heating. The decline in cell viability with increasing temperature shown by the TTC method was consistent with an independently derived count of live cells following temperature treatment and neutral red staining.